2017
DOI: 10.1111/iju.13313
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of single‐session endoscopic combined intrarenal surgery for ipsilateral large renal stones and retrograde intrarenal surgery for contralateral renal stones: Initial experience

Abstract: Carrying out endoscopic combined intrarenal surgery and contralateral retrograde intrarenal surgery in a single session for patients with bilateral stones is feasible and safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…However, the antegrade approach using a flexible ureteroscope or nephroscope can increase the SFRs in cases of acute infundibulopelvic angle or narrow infundibulum, musculoskeletal deformities, or anatomical abnormalities ECIRS can be carried out in either the supine or prone position. However, there has been no randomized controlled study examining the patients’ position ECIRS contains two different concepts of location (bidirectional) and time (simultaneous; Fig. ) Selection of the combined bidirectional or simultaneous bidirectional approach depends on the location and size of the renal stones (Fig.…”
Section: Clinical Questions and Answersmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the antegrade approach using a flexible ureteroscope or nephroscope can increase the SFRs in cases of acute infundibulopelvic angle or narrow infundibulum, musculoskeletal deformities, or anatomical abnormalities ECIRS can be carried out in either the supine or prone position. However, there has been no randomized controlled study examining the patients’ position ECIRS contains two different concepts of location (bidirectional) and time (simultaneous; Fig. ) Selection of the combined bidirectional or simultaneous bidirectional approach depends on the location and size of the renal stones (Fig.…”
Section: Clinical Questions and Answersmentioning
confidence: 99%
“…However, there has been no randomized controlled study examining the patients’ position ECIRS contains two different concepts of location (bidirectional) and time (simultaneous; Fig. ) Selection of the combined bidirectional or simultaneous bidirectional approach depends on the location and size of the renal stones (Fig. ).…”
Section: Clinical Questions and Answersmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors concluded that ECIRS is a novel and excellent procedure in patients with simultaneous renal and ureteral stones, which can increase the stone-free rate and lower morbidity than conventional prone PCNL. Kwon et al [24] performed single-session ECIRS, performed ECIRS for ipsilateral large renal stone, and performed RIRS for treatment of contralateral renal stone. The authors analyzed the results in 26 patients and reported that the stone-free rate of ECIRS was 76.9% (20/26) and the contralateral RIRS was 92.3% (24/26).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, RIRS combined with miniaturized PCNL procedures, such as mini-ECIRS, have been increasing. 79 Although standard PCNL is usually carried out in the prone position, mini-ECIRS is achieved in the prone split-leg position or modified supine Valdivia position. Therefore, there are some differences in the staging of procedures between mini-ECIRS and miniaturized PCNL.…”
Section: Surgical Technique Of Mini-ecirs: How To Do Itmentioning
confidence: 99%